Angiogenesis in zebrafish - Schuermann, Annika; Helker, Christian S. M.; Herzog, Wiebke (Seminars in Cell & Developmental Biology, 2014)
The vasculature consists of an extensively branched network of blood and lymphatic vessels that ensures the efficient circulation and thereby the supply of all tissues with oxygen and nutrients. Research within the last decade has tremendously advanced our understanding of how this complex network is formed, how angiogenic growth is controlled and how differences between individual endothelial cells contribute to achieving this complex pattern. The small size and the optical clarity of the zebrafish embryo in combination with the advancements in imaging technologies cleared the way for the zebrafish as an important in vivo model for elucidating the mechanisms of angiogenesis. In this review we discuss the recent contributions of the analysis of zebrafish vascular development on how vessels establish their characteristic morphology and become patent. We focus on the morphogenetic cellular behaviors as well as the molecular mechanisms that drive these processes in the developing zebrafish embryo. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-09-23
Keywords: Angiogenesis; Blood vessel; Endothelial cell; Guidance; Lumen formation; Zebrafish